Análisis de la relación existente entre la venta de vehículos en Colombia, los desembolsos y el saldo de cartera del crédito de consumo de vehículo : una aplicación para el Banco Finandina en el periodo 2005 A 2017 : (2018)
The objective of this paper is to analyze the effect of the sale of vehicles in Colombia on the disbursements and the balance of the loan portfolio of vehicle consumption at Banco Finandina in the period 2005 to 2017. In 2011, the entity went from being a Commercial Financing Company to a Banking Entity, maintaining its specialization and historical success in the vehicle financing business. The research develops an analysis on the behavior of the vehicle market and the vehicle consumption credit of Banco Finandina. Subsequently, a structural change analysis is carried out and through an Econometric Analysis of Auto-Regressive Vectors (VAR), the effect of the vehicle market on the vehicle consumption credit at Banco Finandina and the effect of the Intervention Rate of the Banco de la República. Finally, the result is complemented with the response impulse functions (IRF). The result shows a structural change in the year 2010 and 2011 of the series total value of disbursements and total value of portfolio balance. The estimate shows that the monthly sale of vehicles has a positive and immediate effect on the disbursements and the balance of the Finandina portfolio. Finally, the Intervention Rate of the Banco de la República presents the expected sign.